CONSTRUCTION OF AN ISLAMIC INDEX USING THE MEDIAN CRITERION OF QUANTITATIVE FILTERS: APPLICATION TO THE AFRICAN STOCK EXCHANGE - Balde, Moustapha; Konte, Mamadou A. (International Journal of Islamic Banking and Finance Research, 2021)
Many techniques, combining qualitative and quantitative filters, have been proposed in the literature to construct an Islamic index on financial stock exchange. These are often based on fixed thresholds to define quantitative filters. However, as companies do not have the same characteristics from one sector to another, it is necessary to have heterogeneous thresholds for filtering purposes. Our contribution, here, is to propose a methodology which integrates this fact by using the median (statistic) criterion which is much more robust than the average criterion (vis-à-vis the presence of extreme values) but also the median statistic is consistent with the Wassatiya principle (50% of the way) than the 33% fraction used by many studies. JEL Classification Codes: G10, G11, G12, G14, G53.